THE PERCEPTION AND PARTICIPATION OF COMMUNITY IN DEVELOPPING SMART ECO-VILLAGE DESTINATION IN THE TOURIST VILLAGE PAKSABALI AS A TOURISM ICON IN KLUNGKUNG DISTRICT-BALI - I Wayan Pantiyasa; Putu Devi Rosalina (Journal of Business on Hospitality and Tourism, 2018)
The development of tourist village is a government policy that is expected to improve the economy of the community, expanding the employment vacancies, alleviating poverty. Expanding the employment vacancies that lead to improve the welfare of rural communities. The purpose of this study is to determine the perception and participation of local people in Paksebali in the development of smart eco-village destination in the tourist village of Paksebali, Dawan subdistrict, Klungkung regency. The approach is done by distributing to 30 respondents (Purposive sampling).The collected data were primary and secondary data with the techniques are observation, interview and documentation. The collected data were then analyzed by qualitative descriptive analysis. The results of this study shows that the public perception of the development of smart eco-village Paksebali tourist village is the the public generally has known about the development of tourist villages. The community very agree and support by implementing the sapta pesona (seven ways of enchantment). People hope that the development of tourist village can promote the village and improve the welfare of their life. Community participation in the development of tourist village is done started from planning, developing facilities and infrastructure, managing, and monitoring and evaluation.